Osteoporosis Prevalence In Stable Patients With Chronic Obstructive Pulmonary Disease - Dwi Handoko; Faisal Yunus; Budhi Antariksa; Rochsismandoko Rochsismandoko (Respiratory Science, 2021)
Background: Chronic obstructive pulmonary disease (COPD) is a major cause of morbidity and mortality in the world. Comorbid diseases in COPD contributing to low health status, affecting the duration of treatment and even death. Osteoporosis is a quite often comorbid that found in COPD. In Indonesia, there are no data of prevalence on osteoporosis in patient with stable COPD. The aim this research to get the data of osteoporosis in patients with stable COPD at Persahabatan Hospital. Method: The studie’s design was cross-sectional. Patients with stable COPD who came to the Asthma/COPD policlinic at Persahabatan Hospital who meet the criteria of inclusion and exclusion. Subjects had an examined of bone mineral density using dual energy x-ray absorptiometry (DXA) and had an examined of vitamin D blood level. At the time of visit, conducted anamnesis of symptoms, exacerbations, history of smoking, used of corticosteroid (oral or inhaled), comorbid, assessment of nutritional status. Results: Subjects were dominated with male (90.6%) in the age group 65-75 years old (53.1%), and smoking history (84.4%). The most degree of COPD were GOLD II (46.9%) and group B (50%) that using corticosteroid (65.7%). Prevalence of osteoporosis was 37.5%. There were no statistically significant between COPD group, the degree of COPD, sex, smoking history, history of corticosteroid, age, levels of 25-OHD, pulmonary function with the occurrence of osteoporosis in patients with stable COPD. There were a statistically significant on low BMI as a risk factor for osteoporosis in stable COPD. Conclusion: The prevalence of osteoporosis in patients with stable COPD in the Persahabatan Hospital is 37.5%. There are a statistically significant relationship between BMI with osteoporosis in patients with stable COPD.